Environmental ethics : intercultural perspectives - Ip, King-Tak. (Value Inquiry Book Series, 2009)
This book shows that environmental protection is a global concern that must enlist all of humanity's cultural, religious, and moral resources. The nine essays in this volume explore the foundations of environmental ethics in the Western philosophical tradition as well as from the perspectives of Christianity, Islam, Daoism, and Buddhism and propose morally responsible attitudes towards nature and the environment.